2021
DOI: 10.1093/ckj/sfab116
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring anti-PLA2R antibody titres to predict the likelihood of spontaneous remission of membranous nephropathy

Abstract: Rationale & Objective In antiPLA2R membranous nephropathy (MN), there is controversy whether spontaneous remission (SR) can be predicted using a single titer, or assessing the dynamic changes anti-PLA2Rab titers. The study objective was to identify the optimal dynamics of anti-PLA2Rab titer to predict SR in MN Patients and Method 127 nephrotic patients with antiPLA2R-MN were prospectively followed-up for 6 months under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Patients with high PLA2R-IgG titer is associated with bad renal function and not easily remission. Jatem-Escalante et al (2021) found the model including baseline anti-PLA2Rabs and a reduction ≥15% at three months for predicting spontaneous remission with a sensitivity of 93% and a specificity of 80%, which was better than changes of proteinuria in the same period of time. Our study indicated the higher the PLA2R-IgG4 titer and the decline ratio of PLA2R-IgG4 as well as the lower the eGFR, the more likely the inefficacy.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Patients with high PLA2R-IgG titer is associated with bad renal function and not easily remission. Jatem-Escalante et al (2021) found the model including baseline anti-PLA2Rabs and a reduction ≥15% at three months for predicting spontaneous remission with a sensitivity of 93% and a specificity of 80%, which was better than changes of proteinuria in the same period of time. Our study indicated the higher the PLA2R-IgG4 titer and the decline ratio of PLA2R-IgG4 as well as the lower the eGFR, the more likely the inefficacy.…”
Section: Discussionmentioning
confidence: 87%
“…But with the discovery of PLA2R and the knowledge advancement on pathogenic mechanism, the PLA2R antibody is regarded as a potential clinical indicator to assess and predict the remission of PLA2R associated IMN, regardless of spontaneous remission or response to immunosuppressive therapy. Although many studies currently are underway or have been published to determine the cut-off value of the PLA2R antibody to predict the remission, no consensus has been reached ( Dahan et al, 2017 ; Jatem-Escalante et al, 2021 ). A recent study indicated that when setting a threshold value for PLA2R antibody detected by ELISA at baseline to 97.5 RU/mL had a sensitivity of 71% and a specificity of 81% to predict the spontaneous remission at the 12th month ( Jatem-Escalante et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these eight studies involving 1237 patients, six studies reported prognostic prediction models on renal function deterioration [ 5 , 6 , 7 , 8 , 9 , 17 ], while the other two reported prediction models on proteinuria remission [ 18 , 19 ]. Five and three of the eight studies were retrospective and prospective, respectively.…”
Section: Resultsmentioning
confidence: 99%